Aktivitas Sosial Ekonomi Penambang Pasir di Tapa Tahun 1998-2010 - Hasan, Renol; Hasan, Refliyanto; Latif, Fikriyanto R. (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2023)
This study aims to determine the socio-economic activities of sand miners in Tapa, Kabila District, Bone Bolango Regency in 1998-2010. The method used in this study is the historical method. Steps such as heuristics, namely collecting and seeking information from secondary sources and secondary sources. Primary sources are obtained orally, such as interviews with informants who are directly involved in the sand miners in Tapa. Primary source The results of the study describe that the sand mining activities in Tapa that have been occurring so far are very closely related to the socio-economic conditions of the people who develop in the region. The monetary crisis in 1998 had a real impact on the community by dropping the prices of the plantation commodities they planted. The beginning of its emergence was indeed as a response from the community from economic uncertainty. Entering the 2000s, sand mining activities experienced a peak with many transport trucks operating in a day. This phenomenon indicates that the community is highly dependent on this extractive activity. in 2008 the sand miners moved to the GORR bridge which is now in Tapa. The miners used traditional tools until 2008, from 2008 to 2010. They used electronic devices, namely using machines to take sand from the river.